PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PELAKSANAAN PEMBELAJARAN - Dasrulisman Dasrulisman (JURNAL PENDIDIKAN ROKANIA, 2017)
Initial observation conducted at SD Negeri 021 Rokan IV Koto, teachers in the school utilize the school environment as a source of learning only two to three times in one semester. Teachers often present lessons in the classroom even though the material presented relates to the school environment. From interviews, most teachers are reluctant to invite students to study outside the classroom, because of the difficult reasons to supervise. In addition there are teachers who convey that they can not and do not know in utilizing the school environment as a source of learning. The type of research is school action research with the sample of research is as many as 13 people. Based on the results of analysis and discussion of cycle I and cycle II mentioned above, it can be concluded that: There is an increase in the ability of Indonesian teachers in the learning process through the Discussion approach at SD Negeri 021 Rokan IV Koto.